2001
DOI: 10.1002/nau.2198
|View full text |Cite
|
Sign up to set email alerts
|

The risk of lower urinary tract symptoms five years after the first delivery*

Abstract: The first pregnancy and delivery may result in stress and urge incontinence 5 years later. Women with stress and urge incontinence 3 months after the first delivery have a very high risk of long-lasting symptoms. An episiotomy or a vacuum extraction at the first delivery seems to increase the risk. Subsequent childbearing or surgery seems without significant contribution. Long-lasting urgency, diurnal frequency, or nocturia cannot be predicted from onset during the first pregnancy or puerperium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
3
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 176 publications
(381 reference statements)
3
78
3
8
Order By: Relevance
“…12 Têm sido implicadas alterações mecânicas e hormonais. As alterações mecânicas estão relacionadas com o aumento da pressão intra-abdominal e as respetivas repercussões no pavimento pélvico.…”
Section: Discussionunclassified
“…12 Têm sido implicadas alterações mecânicas e hormonais. As alterações mecânicas estão relacionadas com o aumento da pressão intra-abdominal e as respetivas repercussões no pavimento pélvico.…”
Section: Discussionunclassified
“…One 5-year prospective study with 278 primiparae reported that the prevalence of nocturia, twice or more during the night, did not increase (2% at a 5-year follow up). 81 …”
Section: Agingmentioning
confidence: 99%
“…Urogenital symptoms are common during pregnancy and the prevalences of the di¡erent symptoms increase with gestational age [Sampselle et al, 1996;Cardozo and Cutner, 1997;Hojberg et al, 1999;Viktrup, 2002]. Urogenital symptoms represent disorders in the normal micturition cycle and can be divided into storage, voiding, and post-micturition symptoms [Abrams et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Urogenital symptoms represent disorders in the normal micturition cycle and can be divided into storage, voiding, and post-micturition symptoms [Abrams et al, 2002]. The prevalences of urogenital symptoms during pregnancy are high but vary depending on the de¢nitions used, the study design and the target population [Cutner et al, 1992;Sampselle et al, 1996;Hojberg et al, 1999;Thorp et al, 1999;Sze et al, 2002;Viktrup, 2002].…”
Section: Introductionmentioning
confidence: 99%